2007
DOI: 10.1080/00140130701235232
|View full text |Cite
|
Sign up to set email alerts
|

A self-analysis of the NASA-TLX workload measure

Abstract: Computer use and, more specifically, the administration of tests and materials online continue to proliferate. A number of subjective, self-report workload measures exist, but the National Aeronautics and Space Administration-Task Load Index (NASA-TLX) is probably the most well known and used. The aim of this paper is to consider the workload costs associated with the computer-based and paper versions of the NASA-TLX measure. It was found that there is a significant difference between the workload scores for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(76 citation statements)
references
References 5 publications
0
70
0
6
Order By: Relevance
“…In this respect it may be useful to include in future studies a workload index, as discussed in several recent studies (Pretorius & Cilliers, 2007;Noyes & Bruneau, 2007 ;Roth, Scott, Deutsch, Kuper, Schmidt, et al ., 2006). Thus, though no direct relation may exist between the present results and real-job performance, the neuropsychological tests enabled suitable outcome measures reflecting cognitive processes also involved in real-job operations.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect it may be useful to include in future studies a workload index, as discussed in several recent studies (Pretorius & Cilliers, 2007;Noyes & Bruneau, 2007 ;Roth, Scott, Deutsch, Kuper, Schmidt, et al ., 2006). Thus, though no direct relation may exist between the present results and real-job performance, the neuropsychological tests enabled suitable outcome measures reflecting cognitive processes also involved in real-job operations.…”
Section: Discussionmentioning
confidence: 99%
“…The original NASA-TLX consists of two parts: rating each aspect, and comparing them pairwise based on their perceived importance. However, it has been shown that the unweighted and the weighted ratings have a high correlation (Noyes and Bruneau 2007). In this study, the outcome of the NASA-TLX was calculated based on the unweighted ratings.…”
Section: Study Setupmentioning
confidence: 99%
“…Type I were the least severe collisions while Type III were of highest severity. The self-reported, survey-based NASA-TLX subjective workload index along with its four subscales (Mental Demand [TLX-MD], Physical Demand [TLX-PD], Effort [TLX-E], and Frustration [TLX-F]) were used as subjective dependent variables [28][29][30].…”
Section: Dependent Variablesmentioning
confidence: 99%